ANALISIS POLA DAN MANAJEMEN KEUANGAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNJ: KEINGINAN VS KEBUTUHAN - Putri, Inqy Azzahra (Universitas Dharmawangsa, 2024)
Abstract: This study analyzes the pattern and financial management of students of the Faculty of Economics, State University of Jakarta (FEB UNJ) with a quantitative descriptive approach through a questionnaire to 50 respondents. With the aim of knowing the source of funds, financial management patterns, and identifying challenges faced by students. The results show that the majority of students are not optimal in managing finances, such as not regularly recording expenses, having difficulty distinguishing needs and wants, and being influenced by external factors such as advertisements. Students also rarely use financial applications, although some have set aside funds for savings or investment. The main challenges faced include limited funds until the end of the month and lack of participation in financial education. This study recommends intensive financial education, the use of financial technology, and improved financial literacy to support better financial management of university students.